1968
DOI: 10.1107/s0567740868002840
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bond studies. XX. The crystal structure of ammonium formate

Abstract: The crystal structure of ammonium formate has been determined at room temperature from threedimensional single-crystal X-ray data. Two HCOONH4 units crystallize in a monoclinic unit cell of space group Pc and dimensions a=3.814, b=4.679, c=9.112A,, and B=91"17 °. The structure was refined by the method of least squares with allowance for anisotropic thermal motion, and gave a final discrepancy index of 0-067. The ammonium ion forms four hydrogen bonds N+-H • • • O-of length 2-81-2.89 A,, in an approximately te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Both are symmetrical and perfectly planar. The dimensions of the formate ion are similar to those occurring in ammonium formate 30 (Table 3) are well within the normal range for strong NH-O hydrogen bonds with the former being slightly stronger and more accurately linear. The orientation of ions within each layer is consistent but this is reversed in alternate layers resulting in an overall centrosymmetric structure.…”
Section: Resultssupporting
confidence: 59%
“…Both are symmetrical and perfectly planar. The dimensions of the formate ion are similar to those occurring in ammonium formate 30 (Table 3) are well within the normal range for strong NH-O hydrogen bonds with the former being slightly stronger and more accurately linear. The orientation of ions within each layer is consistent but this is reversed in alternate layers resulting in an overall centrosymmetric structure.…”
Section: Resultssupporting
confidence: 59%
“…C-O bond lengths of 1.2496(12) and 1.2502(13) Å, respectively, are nearly identicaldue to resonancestabilization of thecarboxylate. These values are, therefore,found to be slightly longer thanthe correspondingb ond lengthsa tr oomt emperature fort his compound that were reported to be around 1.23-1.24 Å [2]. All of the nitrogen-bound hydrogen atomsp articipate in hydrogen bonds with both oxygen atomsofthe formiate anion acting as acceptors.…”
Section: Discussionmentioning
confidence: 62%
“…To allow for the comparison of the influence of hydrogen bonding on structural parameters, the ammonium salt of this acid was chosen as astarting point. Although the structure of the latter compound has been determined earlier, data is only availableatroomtemperature [2]. As molecular and crystal structures of target molecules are to be determined at low temperature, the structure of the title compound was re-determined to enable comparisons of individual metrical parameters throughout the whole series.…”
Section: Discussionmentioning
confidence: 99%
“…A recent CSD survey has shown that the RING motif is observed in 95 % of the structures of neutral carboxylic and polycarboxylic molecules. [22] A notable exception is acetic acid which forms the CHAIN motif in the solid state, [23] although it has been demonstrated by theoretical calculations that the acetic acid RING is favoured over CHAIN by approximately 3 kcal mol À1 . [24a] These differences were explained by invoking the contribution of other weak intermolecular interactions in the solid state with respect to the structure of the isolated dimers in a vacuum.…”
Section: Resultsmentioning
confidence: 99%